Performance of polyethylene glycol (PEG) capped zinc oxide nanoparticles as photocatalyst in membrane photocatalytic reactor for industrial dye wastewater treatment - Desa, Amira Liyana (2020)
Zinc oxide (ZnO) nanoparticles have gained immense research interest because of its high photocatalytic efficiency, inexpensive material and environmentally friendly characteristics. Several capping agents were used on ZnO nanoparticles to solve the problem concerning the agglomeration and aggregation. Nowadays, there is no study involving the effect of polyethylene glycol (PEG) as capping agent on ZnO nanoparticles via precipitation method in the application of membrane photocatalytic reactor (MPR) system. Therefore, this research focused on the effectiveness of PEG capped on ZnO as photocatalyst in MPR for treating dye wastewater from textile industry in Johor, Malaysia. Three different ZnO were utilized in the present study which are commercial ZnO, zinc oxide in the presence of polyvinylpyrrolidone (ZnOPVP) and zinc oxide in the presence of polyethylene glycol (ZnO-PEG) nanoparticles in order to evaluate their effectiveness and effect on the membrane filtration process. Overall, it was found that ZnO-PEG nanoparticles and polypiperazine amide ultrafiltration (UF-PPA) membrane were presented as a great approach in improving normalised flux reduction (58.67%) at best operating condition and produced excellent permeate quality in terms of dye removal (100%), turbidity removal (100%), chemical oxygen demand (COD) reduction (97.37±0.06%) and total dissolved solids (TDS) removal (92.34±0.01%). The best operational conditions of MPR occurred at pH 11 of feed wastewater and 0.10g/L of ZnO-PEG loading with 6 bars of inlet pressure. The overall results were supported by Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM) and contact angle analysis which confirmed that ZnO-PEG nanoparticles has great potential in improving fouling phenomenon of UF-PPA process in MPR. Moreover, it was proved that the both stages of normalised flux during the best conditions fitted well with the cake filtration model according to Wiesner and Aptel equations. Hence, ZnO-PEG nanoparticle was found to assist on the reduction of membrane fouling and achieve excellent permeate quality using MPR system for industrial dye wastewater.